A Roadmap for Cloud Computing Migration in Yemeni Universities Using the ROCCA Model - Nabil Almekhlafi; Abdullah Hussein Al-Hashedi; Ahmed Abdullah Farhan Mhoub (University of Science and Technology, Sana'a, Yemen, 2025)
This paper explores the implementation of cloud computing in Yemeni universities, leveraging insights from the Roadmap for Cloud Computing Adoption (ROCCA) model to address the unique needs of academic institutions. Cloud computing offers significant benefits, including scalability, cost efficiency, enhanced collaboration, and improved access to resources, which are essential for supporting research, teaching, and administrative functions. However, the migration to cloud computing presents challenges such as data security, regulatory compliance, and managing diverse workloads. To address these complexities, this paper proposes a tailored framework for cloud computing migration, spanning the entire lifecycle from analysis and design to adoption, migration, and management. The findings underscore that a well-planned and executed cloud computing strategy can enhance institutional flexibility, security, and operational efficiency, enabling higher education institutions to fully harness the transformative potential of cloud technologies while mitigating associated risks. This framework provides actionable guidelines and best practices to support academic institutions in achieving a successful and sustainable transition to cloud-based systems.